2021
DOI: 10.3393/ac.2019.06.18
|View full text |Cite
|
Sign up to set email alerts
|

Increased Long-term Risk of Anal Fistula After Proctologic Surgery: A Case-Control Study

Abstract: Purpose: Anal fistula is a common condition in proctology, usually requiring surgical treatment. Few risk factors have been clearly identified based on solid evidence. Our research objective was to determine whether history of anal surgery was a risk factor for subsequent anal fistula.Methods: We conducted a case-control study from January 1, 2012 through December 31, 2013 in our tertiary center, comprising 280 cases that underwent surgery for anal fistula and 123 control patients seeking a consultation for up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A medical history of prior proctological surgery did not seem to be a risk factor of postoperative bleeding in our study. Little is known about this issue and the medical literature has little data although one recent study suggested that previous history of anal surgery was highly associated with the risk of anal fistula [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A medical history of prior proctological surgery did not seem to be a risk factor of postoperative bleeding in our study. Little is known about this issue and the medical literature has little data although one recent study suggested that previous history of anal surgery was highly associated with the risk of anal fistula [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…If possible, surgical procedures should be delayed until a few weeks after delivery. It would be advantageous to avoid potential complications associated with hemorrhoidectomy [18,19].…”
Section: Conservative Treatmentmentioning
confidence: 99%